La TraducciÃ³n De La ArgumentaciÃ³n En El Texto PeriodÃstico EspaÃ±ol/Ãrabe Y La AplicaciÃ³n De Las TÃ©cnicas EspecÃficas De TraducciÃ³n - Baya E, Moulay-Lahssan (European Scientific Journal, ESJ, 2016)
This research aims at presenting the importance of the journalistic translation from Spanish into Arabic. It pretends to present this topic through two main axes. The first axe presents a contextualization of journalistic genre in a very particular way; the argumentative genre as the main axe of our research. The second axe of this work, which has been very practical, after defining and exposing the characteristics of argumentative text, focuses on the application of specific techniques of journalistic translation, which are basically, amplification, compression and omission. Therefore, we have chosen a mass media of great international projection: Project Syndicate; an international organization that has the largest source of world opinion articles in different languages, signed by eminent intellectuals and specialists in different fields of knowledge. Subsequently, we proceeded to the selection of news argumentative and we have analyzed the translation technique used in each case, with its pertinent comments as final results of the study.